Edible insects as food of the future - Prokopenko, V. V. (ТДАТУ, 2020)
It is important to emphasize that recently the consumption of meat in the world has grown significantly, respectively, to meet the demand in such volumes, the amount of resources required for breeding animals and their subsequent processing has increased, which has led to global deforestation, pollution and an increase in the level greenhouse gas emissions. The use of insects for food may meet the human need for protein-containing products, but the conditions for their breeding require further study.
Keywords: edible insects; nutritional content; caterpillars; Rhynchophorus phoenicis